Ubuntu philosophy as a strategy to promote access to under-five child healthcare services - Tshivhase, Livhuwani; Moyo, Idah (Curationis (Pretoria), 2025)
Background Inaccessibility of healthcare services for children under five contributes to child morbidity and mortality in sub-Saharan Africa. Children are reportedly dying at home from treatable conditions, hence the need for this study. Objectives The study aimed to exploring and synthesising the barriers in accessing under-five child healthcare services through the lens of ubuntu philosophy in sub-Saharan Africa. Method An integrative literature review was conducted. Several databases were searched utilising a combination of phrases such as: ‘access’, ‘barriers’, ‘child healthcare services’ and ‘sub-Saharan Africa’. Qualitative and quantitative studies, published between 2014 and 2024 in sub-Saharan Africa, were used. Results Study findings revealed that there were parental- or guardian-related factors, healthcare provider factors and healthcare environment factors that can hinder access to healthcare services for children under the age of five. Conclusion Intervention measures to address the barriers to access of healthcare services by children under five should embed ubuntu values by all healthcare providers and policymakers. Continuous health education to empower parents and guardians on childcare practices is recommended. Contribution The study provides insights into challenges of accessing child healthcare services. These findings are key for nurse managers, nurse educators and policymakers to better plan for comprehensive quality service provision. Leveraging on Ubuntu philosophy would be pivotal to making a critical analysis of these challenges and how to address them.